VD_FINDINFO Pron / 2012 / 163 vom 30. Juli 2012 - VD Tribunal cantonal (2012)
TRANSACTIONACCORD, PROTECTION DE L'UNION CONJUGALE, FRAISEN GÉNÉRAL | 105 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)